1968
DOI: 10.3758/bf03328225
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking strategies in cognitive development

Abstract: The information seeking strategies of six-, seven-, and eight-year Bruner (1966) argued that the thinking of young children is largely dependent upon perceptible aspects of the environment. Thus, when a child seeks relevancy or information we might expect his search to be guided by those features which can be "seen" in the situation rather than those which must be abstracted from it. Mosher & Hornsby (1966) investigated this possibility using the old parlor game of 20 Questions. They found that when faced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
1
13
1
Order By: Relevance
“…The only respect in which the present study differed importantly from Van Horn and Bartz (1968) was that in the present study each 2 was given all four arrays, whereas in the previous study one group of ^s was given the ordered array and another group was given the random array.…”
Section: Experiments 1 Eachcontrasting
confidence: 40%
See 4 more Smart Citations
“…The only respect in which the present study differed importantly from Van Horn and Bartz (1968) was that in the present study each 2 was given all four arrays, whereas in the previous study one group of ^s was given the ordered array and another group was given the random array.…”
Section: Experiments 1 Eachcontrasting
confidence: 40%
“…In a situation similar to that used by Mosher and Hornsby (I966), Van Horn and Bartz (1968) found that six-year-olds would use the under lying features of a task to establish informational constraints only when those features were perceptually obvious. Eight-year-olds, on the other hand, took advantage of these underlying features regardless of whether or not they could be "seen" in the situation.…”
Section: )mentioning
confidence: 81%
See 3 more Smart Citations